2020
DOI: 10.1016/j.jpag.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Turner Syndrome with Y Chromosome: Spontaneous Thelarche, Menarche, and Risk of Malignancy

Abstract: Study Objective: Girls with Turner syndrome with Y-chromosome material (TS + Y) are assumed to have nonfunctional gonads with increased tumor risk, therefore prophylactic gonadectomy is recommended at diagnosis. In this study we aimed to determine rates of spontaneous thelarche (ST) and spontaneous menarche (SM), and prevalence of gonadal tumor and malignancy in girls with TS + Y, to further inform discussions about gonadectomy. Design: Retrospective review of clinical and pathology data. Setting: Multicenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…Remarkably, a spontaneous pregnancy has been reported in a female with a predominantly 46,XY karyotype, including in the gonad (95% 46,XY) [141]. A recent study of 44 individuals with Turner syndrome and presence of Y chromosome material found spontaneous menarche in 2/26 (7.6%) of those with a 45,X/46,XY karyotype, although the potential for fertility in these individuals was not reported [142].…”
Section: X/46xymentioning
confidence: 99%
“…Remarkably, a spontaneous pregnancy has been reported in a female with a predominantly 46,XY karyotype, including in the gonad (95% 46,XY) [141]. A recent study of 44 individuals with Turner syndrome and presence of Y chromosome material found spontaneous menarche in 2/26 (7.6%) of those with a 45,X/46,XY karyotype, although the potential for fertility in these individuals was not reported [142].…”
Section: X/46xymentioning
confidence: 99%
“…We also analysed bone mineral density in subjects with the 45,X karyotype (n = 28) and compared it with that in subjects with a karyotype other than 45,X (n = 75) because the incidence of spontaneous menarche was previously reported to be low in those with the 45,X karyotype. 14 However, as shown in Table S1, bone mineral density did not significantly differ between the two groups even after adjustments for age, BMI and the presence of spontaneous menarche. Abbreviations: BMD, bone mineral density; aBMD, areal BMD; vBMD, volumetric BMD.…”
Section: Bone Mineral Density Is Higher In Young Adults With Ts Who Showed Spontaneous Menarchementioning
confidence: 83%
“…These results suggest that spontaneous menarche is important for the acquisition of better bone mineral density in young adults with TS independent of age and BMI. We also analysed bone mineral density in subjects with the 45,X karyotype ( n = 28) and compared it with that in subjects with a karyotype other than 45,X ( n = 75) because the incidence of spontaneous menarche was previously reported to be low in those with the 45,X karyotype 14 . However, as shown in Table S1, bone mineral density did not significantly differ between the two groups even after adjustments for age, BMI and the presence of spontaneous menarche.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if the patient has clitoromegaly or masculinized genitalia at birth and virilization at puberty, the possibility of Y chromosome mosaicism should be investigated [10]. If Y chromosome mosaicism is present, the risk of developing gonadoblastoma or dysgerminoma is 10-20% in the second decade of life [7][8][9][10]. The risk increases with increasing age, and the risk of developing gonadoblastoma in dysgenetic gonads increases up to 30% [9][10][11].…”
Section: Introductionmentioning
confidence: 99%